Pancreatic Aetiology for Massive Upper Gastrointestinal Haemorrhage in Pregnancy. (29th February 2016) - Zaborowski, Alexandra; Walsh, Siun M.; Ravi, Narayanasamy; Reynolds, John V.
Abstract : We present herein what we believe is the first reported case of massive upper gastrointestinal bleeding in pregnancy due to a pancreatic neuroendocrine tumour causing left sided portal hypertension. A 37-year-old 27-week pregnant female presented with massive haematemesis and melaena requiring transfusion of 10 units of red cell concentrate. Gastric varices were evident at endoscopy. An MRI revealed a large mass infiltrating the pancreatic tail and spleen with massive upper abdominal varix formation secondary to splenic vein invasion. A caesarean section was performed, followed by a radical en bloc partial pancreatectomy and splenectomy with resection of the fundus of the stomach and ligation of gastric and splenic varices. Her postoperative course was uncomplicated. Histology revealed a well differentiated grade 2 neuroendocrine tumour with final staging of T4N0. This case highlights an infrequently encountered cause of massive gastrointestinal bleeding. Diagnosis and management of pancreatic neuroendocrine tumours, due to their rarity and variable clinical presentation, can be challenging particularly in the setting of pregnancy where the wellbeing of a second patient must also be considered. A multidisciplinary approach with input from obstetricians and general surgeons is required when deciding optimum management, while also taking into account the patient's preferences.